STRATEGY OF COMMUNITY ECONOMY EMPOWERMENT THROUGH THE MANAGEMENT OF WAQF ASSETS AT THE BAITUSSALIHIN MOSQUE IN ULEE KARENG, BANDA ACEH CITY - Samad, Fauzan; Khotimah, Umi Khusnul; Khan, M. Dawud Arif; Mukhtar, Makmunzir (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This study aims to explore the strategies for empowering the community's economy through the management of waqf assets at Baitussalihin Mosque in Ulee Kareng, Banda Aceh City. The problem formulation encompasses the challenges and opportunities in empowering the community's economy through waqf, focusing on the role of Baitussalihin Mosque as a center of activities and a symbol of philanthropy in its community. The research method used is qualitative descriptive with a case study approach, including interviews, document studies, and participant observation. The main findings highlight important strategies that can be applied, including increasing community participation through extensive socialization, enhancing the competence of waqf managers, collaboration with third parties, improving administrative systems with clear regulations, and utilizing modern technology in waqf management. It is hoped that the holistic implementation of these strategies can significantly contribute to empowering the community's economy through waqf resources, with the potential to enhance the welfare of the community as a whole.